2023
DOI: 10.1021/acs.energyfuels.3c02178
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Polyvinyl Alcohol–Phenolic Aldehyde–Polyacrylamide Gel for the Application in Saline Oil Reservoirs for Profile Modification

Shuyang Dong,
Long He,
Liang Li
et al.

Abstract: Polymer gels are widely used in the oil and gas industry, and high-molecular-weight polymer gels have significant effects on reservoir water plugging operations. Based on nontoxic polyvinyl alcohol (PVA), its stability in solvents containing formation saltwater (Tahe oilfield, NW China) was studied, and the composite gel solution was prepared using saltwater. The polymerization mechanism of PVA with phenolic resin (PF) and polyacrylamide (PAM) was analyzed, using hexamethylenetetramine (HMTA) instead of formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…Moreover, its effect on the gelation time and gel strength were analyzed (Figure 3). The gel strength codes (A-I) of the bottle test were converted into numerical values (1)(2)(3)(4)(5)(6)(7)(8)(9). The results showed that there was a noticeable upward trend in both the gelation rate and gel strength as the hydrodynamic radius of the HPAM increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, its effect on the gelation time and gel strength were analyzed (Figure 3). The gel strength codes (A-I) of the bottle test were converted into numerical values (1)(2)(3)(4)(5)(6)(7)(8)(9). The results showed that there was a noticeable upward trend in both the gelation rate and gel strength as the hydrodynamic radius of the HPAM increased.…”
Section: Resultsmentioning
confidence: 99%
“…An effective solution to mitigate or eliminate this problem is polymer gel treatment [ 4 , 5 , 6 , 7 ]. Polymer gels can be categorized into inorganic crosslinked gels and organic crosslinked gels based on the type of crosslinker employed [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Marinković et al conducted a composite hydrogeothermal investigation of the post-Neotethys Late Paleogene Neogene crustal core complex in the Kopaonik Mountains of the southwestern Serbian Plateau. The fractured carbonate reservoirs in Tahe Oilfield are different from conventional porous sandstone reservoirs and other karst carbonate reservoirs. The main storage space of oil reservoirs is mainly composed of cracks and caves formed by structural deformation and collapse, as well as pores and caves formed by karst processes. The large karst caves are the most important storage space, and cracks are the main connecting channels. Due to the different types of karst caves and cracks of different scales, their morphology and scale are different, making it difficult to establish a unified geological model using a single method. Therefore, different modeling methods are used to establish discrete models for different constituent elements. Then, the discrete models were integrated into a wpore, establishing a three-dimensional distribution model of the fractured and vuggy reservoir. …”
Section: Introductionmentioning
confidence: 99%
“… 34 38 Therefore, different modeling methods are used to establish discrete models for different constituent elements. 37 38 39 Then, the discrete models were integrated into a wpore, establishing a three-dimensional distribution model of the fractured and vuggy reservoir. 45 56 …”
Section: Introductionmentioning
confidence: 99%